Decolonizing school psychology research: A systematic literature review. (17th June 2022) - Grant, Stephanie; Leverett, Patrice; D'Costa, Stephanie; Amie, Kandyce Anderson; Campbell, Stephanie McCullough; Wing, Sydney
Abstract: School Psychologists are called to increase the well‐being of clients they serve. However, despite a focus on supporting academic and behavioral success, school psychology has been used to enforce Eurocentric standards of normalcy and behavior on students in schools, punishing and excluding those deemed different. "Othering" is rooted in a legacy of educational indoctrination and assimilation negatively impacting students from minoritized backgrounds and represents a "colonial present". To evaluate the epistemic violence endemic to school psychology, we conducted a systematic literature review of the most recently published literature across five school psychology journals ( n = 627) utilizing a decolonial framework. Articles were coded for demographic inclusion, empirical approach, disciplinary context, minoritized inclusion level, and acknowledgment of author situatedness and roles in maintaining colonialist structures. While, 81% of studies included some degree of minoritized inclusion, less than 5% of these articles utilized culturally responsive approaches or acknowledged colonialism or white supremacy. Recommendations for a movement toward a more decolonial approach to school psychology research are discussed.